WATER QUALITY STATUS IN TANJUNG BUTON PORT AREA BASED ON SEA WATER QUALITY INDEX (IKAL) - Lestari, Tri Ayu; Adriman, Adriman; Fauzi, Muhammad (Journal of Environmental Engineering and Sustainable Technology, 2024)
Tanjung Buton Port is one of the ports with considerable potential to support national development. The water quality status in the Tanjung Buton Port area is suspected to be declining, water quality due to activities in the port area. So, this study aims to determine the status of water quality in the Tanjung Buton Port area based on the Sea Water Quality Index. The research was conducted in October - November 2023 in the Tanjung Buton Port Area in Sungai Apit Regency, Riau Province. Determination of water quality status uses the Marine Water Quality Index (WQI) method. This research will be conducted at three measurement and sampling stations, where one sampling will be done at each station. Measurements and sampling are carried out at low tide. Parameters observed include temperature, pH, DO, salinity, TSS, total ammonia, oil and grease, and ortho-phosphate.  The condition of Tanjung Buton Harbor water quality status in this study based on the Marine Water Quality Index (WQI) is included in the "moderately polluted" category with WQI ranging from 50.01-55.38. Based on the research results, it is recommended that the government and the management of Tanjung Buton Port pay attention to the management of pollutant sources around Tanjung Buton Port.